The iron giant [videorecording (Blu-Ray)] - Bird, Brad, 1957-; McCanlies, Tim; Kamen, Michael; Fucile, Tony; Hughes, Ted, 1930-1998 (Warner Bros. Entertainment Inc., 2016)
A giant robot from outer space lands on Earth and frightens a small town. The robot befriends a young boy and wins its humanity by saving the townspeople from their own fears and prejudices. Includes deleted scenes and commentary from director Brad Bird. Also includes theatrical version in addition to signature edition version.